A wearable point-of-care system for home use that incorporates plug-and-play and wireless standards. - Jianchu Yao (IEEE Transactions on information technology in biomedicine)
A point-of-care system for continuous health monitoring should be wearable, easy to use, and affordable to promote patient independence and facilitate acceptance of new home healthcare technology. Reconfigurability, interoperability, and scalability are important. Standardization supports these requirements, and encourages an open market where lower product prices result from vendor competition. This paper first discusses candidate standards for wireless communication, plug-and-play device interoperability, and medical information exchange in point-of-care systems. It then addresses the design and implementation of a wearable, plug-and-play system for home care which adopts the IEEE 1073 Medical Information Bus (MIB) standards, and uses Bluetooth as the wireless communication protocol. This standards-based system maximizes user mobility by incorporating a three-level architecture populated by base stations, wearable data loggers, and wearable sensors. Design issues include the implementation of the MIB standards on microcontroller-driven embedded devices, low power consumption, wireless data exchange, and data storage and transmission in a reconfigurable body-area network.